Legal Protection for Patients Undergoing Orthopedic Surgery from The Perspective of Equity and Sustainability in Health Care - Nucky Indra Praja (Jurnal Sosial Teknologi, 2026)
In healthcare practice, orthopedic surgical procedures are frequently performed on patients with serious injuries, such as work-related accidents or traffic accidents, which require immediate medical attention. However, postoperative complications are often perceived as medical malpractice, potentially leading to disputes between patients and medical personnel. This situation highlights the lack of clarity regarding the boundary between medical risk and medical negligence, which can give rise to legal liability. This study aims to (1) analyze the legal framework regarding patient protection in orthopedic surgery within the Indonesian healthcare legal system, and (2) examine the boundary between medical risk and malpractice, as well as its implications for healthcare providers’ liability from the perspectives of equity and the sustainability of healthcare services. The research method used was a normative legal study employing both a statutory and a conceptual approach. The results of the study indicate that legal protection for patients undergoing orthopedic surgery is related to the recognition of patients’ rights, the implementation of patient safety measures, and the obligation of medical personnel to provide clear medical information through informed consent. Compliance with professional standards and medical service standards serves as the basis for distinguishing between acceptable medical risks and medical negligence categorized as malpractice. Therefore, strengthening medical service standards, ensuring transparency of information, and establishing fair dispute resolution mechanisms are necessary to guarantee patient protection while also providing legal certainty for medical personnel in delivering equitable and sustainable healthcare services.